Transition-Metal-Catalyzed Cross-Coupling with Non-Diazo Carbene Precursors - Wang, Kang; Wang, Jianbo (Synlett, 2019)
Transition-metal-catalyzed cross-coupling reactions through metal carbene migratory insertion have emerged as powerful methodology for carbon–carbon bond constructions. Typically, diazo compounds (or in situ generated diazo compounds from N-tosylhydrazones) have been employed as the metal carbene precursors for this type of cross-coupling reactions. Recently, cross-coupling reactions employing non-diazo carbene precursors, such as conjugated ene-yne-ketones, allenyl ketones, alkynes, cyclopropenes, and Cr(0) Fischer carbenes, have been developed. This account will summarize our efforts in the development of transition-metal-catalyzed cross-coupling reactions with these non-diazo carbene precursors.1 Introduction2 Cross-Coupling with Ene-yne-ketones, Allenyl Ketones, and Alkynes3 Cross-Coupling Involving Ring-Opening of Cyclopropenes4 Palladium-Catalyzed Cross-Coupling with Chromium(0) Fischer Carbenes5 Conclusion
Keywords: cross-coupling; catalysis; carbene migratory insertion; metal carbene; C–C bond formation